THE VALIDITY OF COMPANYING TEXTBOOK BASED ON BANGKALAN LOCAL WISDOM THE BEAUTY OF DIVERSITY IN MY COUNTRY - Atika Maulidina Hs; Agung Setyawan (Widyagogik, 2022)
One of the criteria for educational products to be said to be feasible and can be used in the classroom is validity. This trial was conducted to measure the suitability of the product with the theory. The purpose of this study was to determine the level of validity of companion textbook products based on Bangkalan local wisdom, the theme of the beauty of diversity in my country. In this study, validity trials were carried out by experts and users with the aspects measured including material, language, textbook design, and culture. From the validity test on these aspects, the expert validity score was 87% and the user validity score was 94%. At the end of the validation stage, an average validity of 90% was obtained, indicating that the companion textbook product was very valid and suitable for use in the classroom.